Obesity-related asthma and its relationship with microbiota - Huang, Jinli; Zhou, Xuehua; Dong, Bo; Tan, Hong; Li, Qiuhong; Zhang, Juan; Su, Hui; Sun, Xin (Frontiers in Cellular and Infection Microbiology, 2024)
Obesity and asthma are global public health problems. Obesity-related asthma is a special phenotype of asthma with a complex pathogenesis. Its occurrence and development are related to mechanical compression, inflammatory response, metabolic regulation, gene regulation, and vitamin D deficiency. Different treatment strategies used in the process of weight loss have a beneficial impact on asthma. Alterations in gut and airway microbial community structure and their metabolites may also contribute to obesity-related asthma. The role of the Th17/Treg balance in the gut microbiota regulating the immune responses and host metabolism is important. Therapeutic measures associated with the gut microbiota variety may contribute to improving chronic inflammation associated with obesity by regulating the Th17/Treg balance. An early reduction in microbial diversity can predict the development of asthma and lead to allergy through an imbalance of Th2/Th1 responses. Short-chain fatty acids (SCFAs) regulate the differentiation and activation of regulatory T cells, thereby regulating immune homeostasis in the lung to suppress allergic inflammation and weight gain. Therefore, clarifying the microbial mechanism of obesity-related asthma has important guiding significance for clinical treatment. In this review, we used the following terms: “asthma and obesity” and “obesity-related asthma”, combining “phenotype”, “airway inflammation” and “lung function”, and reviewed the characteristics and pathogenesis of obesity-related asthma, the relationship between the gut and airway microbiota and obesity-related asthma, and the current treatment measures for the disease.